2008
DOI: 10.1007/s11695-008-9755-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Nutritional Indices and Birth Weight After Roux-en-Y Gastric Bypass

Abstract: (1) Anemia as well as additional nutritional deficits during pregnancy were not totally eliminated, despite dietary guidance and micronutrient supplementation; (2) alleviation of metabolic comorbidities was demonstrated, and improved normalization predicted higher birth weight; (3) energy and folate intake was sufficient, but other nutrients probably did not reach ideal levels; (4) recent dietary guidelines for this population represent a step forward, but additional studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…In cases in which the studies performed both unadjusted linear correlations and adjusted regression coefficients we reported the latter (as B-or b-coefficients), but if only unadjusted correlations were carried out, we reported the former (as r coefficients). One study showed a significant positive correlation (17), and 9 showed no association between vitamin B-12 and BW [2 positive but nonsignificant (103, 108), 5 negative (24,29,61,87,105), and 2 showed varying associations at different time points (96,113)]. …”
Section: Effect Of Vitamin B-12 Concentrations Across the Spectrum On Bwmentioning
confidence: 99%
“…In cases in which the studies performed both unadjusted linear correlations and adjusted regression coefficients we reported the latter (as B-or b-coefficients), but if only unadjusted correlations were carried out, we reported the former (as r coefficients). One study showed a significant positive correlation (17), and 9 showed no association between vitamin B-12 and BW [2 positive but nonsignificant (103, 108), 5 negative (24,29,61,87,105), and 2 showed varying associations at different time points (96,113)]. …”
Section: Effect Of Vitamin B-12 Concentrations Across the Spectrum On Bwmentioning
confidence: 99%
“…[12][13][14][15] The monitoring of nutrient deficiencies after bariatric surgery, despite routine multivitamin supplementation, is important. [16][17][18] Guidelines suggest screening for micronutrient deficiencies annually beginning the year after bariatric surgery. 19,20 There are no prior investigations of laboratory testing for and diagnosis of micronutrient deficiency in women who become pregnant after bariatric surgery.…”
mentioning
confidence: 99%
“…Based on a systematic review to identify literature related to micronutrient deficiencies occurring after bariatric surgery, Shankar and colleagues noted that bariatric surgery patients are at increased risk for deficiency of a number of nutrients following surgery (e.g., vitamin B 12 , folate, and iron) [17]. Consequently, the authors recommended prenatal supplementation for pregnant women who have undergone bariatric surgery due to reported associations between micronutrient deficiencies and maternal and fetal complications, including anemia and low birth weight [17,18]. Indeed, we found a statistically significant association between prior bariatric surgery and delivery of an infant that was SGA (regardless of maternal obesity status), even after controlling for maternal anemia status.…”
Section: Discussionmentioning
confidence: 99%